2015
DOI: 10.1371/journal.pone.0130874
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Season Regional Analysis of Multi-Species Occupancy: Implications for Bird Conservation in Agricultural Lands in East-Central Argentina

Abstract: Rapid expansion and intensification of agriculture create challenges for the conservation of biodiversity and associated ecosystem services. In Argentina, the total row crop planted area has increased in recent decades with the expansion of soybean cultivation, homogenizing the landscape. In 2003 we started the first long-term, large-scale bird monitoring program in agroecosystems of central Argentina, in portions of the Pampas and Espinal ecoregions. Using data from this program, we evaluated the effect of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 60 publications
4
33
0
8
Order By: Relevance
“…It has been demonstrated that agricultural activities may provide benefits for the survival of the Orange River Francolin, provided they are managed properly. This is in accordance with the finding of Goijman et al (2015) that a positive relationship exists between bird species diversity and habitat heterogeneity in agricultural landscapes. Aspects which proved beneficial in this regard were a diversity of crops and pastures with patches of natural areas.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been demonstrated that agricultural activities may provide benefits for the survival of the Orange River Francolin, provided they are managed properly. This is in accordance with the finding of Goijman et al (2015) that a positive relationship exists between bird species diversity and habitat heterogeneity in agricultural landscapes. Aspects which proved beneficial in this regard were a diversity of crops and pastures with patches of natural areas.…”
Section: Introductionsupporting
confidence: 93%
“…Francolins benefit from arable edges (a product of fragmentation) in a number of ways (Goijman et al 2015); (1) weed, soya bean and maize plants provided cover in the edges of arable land so that the francolins could move into these habitats to feed unhindered by predators; (2) open edges probably provided space for marginal francolins which otherwise would have perished due to competition should they have remained in the grass camps during a time when chicks are growing up; (3) arable edges, especially when ploughed, provide food in the form of pieces of weed plants, corms, bulbs and fallen grain which were not found in grass camps (Little 2016). Since the grass camps were grazed quite heavily by cattle limited grass seeds were available for food during late winter which is a period when the francolins moved into arable edges to supplement their diet; (4) the maize fields between grass camps probably provided a buffer between territorial males as these males are actively attracted towards each other by territorial calls in unvaried grass camps (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The approach models detection/non-detection data from multiple species pre-and post-treatment (i.e. Russell et al 2009;Goijman et al 2015). Each species is modeled individually (with species-specific parameters) but also related to other species through the model's hierarchical formulation (Goijman et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A site longitude covariate was included in the modeling to account for some of the possible effects of this bias (i.e. Goijman et al ); however, we consider any confounding factors unlikely to be as important as the main treatment effect, given that introduced foxes and cats are known to be major predators of the Australian avifauna (Dickman ; Woinarski et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Another major crop, soy, also has a large negative impact on biodiversity (242), supporting an impoverished bird diversity compared to natural ecosystems in Brazil and Argentina (243,244). Much of the soy production in Brazil has replaced the high-biodiversity Cerrado grasslands, home to many species found nowhere else (162), despite the Soy Moratorium (245,246).…”
Section: How Does Oil Palm Compare With Other Major Impacts To Biodivmentioning
confidence: 99%